Church and culture: German Catholic theology, 1860 - 1914 - O'Meara, Thomas F. (Univ. of Notre Dame Press, 1991)
Setzt sich u.a. mit der Theologie von Paul Schanz, Herman Schell und Karl Braig auseinander